2022
DOI: 10.1111/imj.15719
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenomic testing: perception of clinical utility, enablers and barriers to adoption in Australian hospitals

Abstract: Background Despite healthcare professionals (HCP) endorsing the clinical utility of pharmacogenomics testing, use in clinical practice is limited. Aims To assess HCP' perceptions of pharmacogenomic testing and identify barriers to implementation. Methods HCP involved in prescribing decisions at three hospitals in Sydney, Australia, were invited to participate. The online survey assessed perceptions of pharmacogenomic testing, including: (i) demographic and practice variables; (ii) use, knowledge and confidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 29 publications
4
13
0
Order By: Relevance
“…Similar findings were also reported in a recent Australian study conducted by Pearce et al. involving non‐oncology‐specific HCPs, where only less than a quarter of the HCPs surveyed received PGx training as part of their undergraduate curricula 43 . This is reasonable given PGx was/is an emerging field despite personalized medicine being recognized for its potential over 2 decades ago.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Similar findings were also reported in a recent Australian study conducted by Pearce et al. involving non‐oncology‐specific HCPs, where only less than a quarter of the HCPs surveyed received PGx training as part of their undergraduate curricula 43 . This is reasonable given PGx was/is an emerging field despite personalized medicine being recognized for its potential over 2 decades ago.…”
Section: Discussionsupporting
confidence: 86%
“…It is possible that the findings may not be generalizable to all HCPs and consumers in oncology as there is evidence that differences exist in the knowledge and practices across different subspecialities, professions, and work settings. 26,29,35 In line with previous studies in noncancer-specific settings, 15,[43][44][45] the results of this systematic review reinforce the notion that utility of PGx testing in oncology is perceived positively by both HCPs and patients. Costs and lack of insurance coverage were found to be the main barriers in adoption of PGx testing in oncology.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…To assess clinical pharmacists’ knowledge of and attitudes toward PGx testing, we conducted this survey among clinical pharmacists practicing at tertiary hospitals across mainland China. We found that most Chinese clinical pharmacists who participated in our survey had a relatively good understanding of and positive attitudes toward PGx testing compared with results presented by similar studies in Saudi Arabia [ 23 ] (knowledge score for all participants was 2.4 out of 5.0), Japan [ 24 ] (only 12.5% respondents showed a good understanding of PGx testing), Thailand [ 25 ], Netherlands [ 26 ], and Australia [ 27 , 28 ] (6–21% pharmacists have knowledge about PGx testing).…”
Section: Discussionsupporting
confidence: 58%
“…35,39,45,47,48,53,56,58,59,83,84 Out of the 34 studies that reported on PGx knowledge or awareness among pharmacists, 23 found that the majority of the respondents had a low or inadequate level of PGx knowledge or awareness. 31,[35][36][37][38]41,44,46,47,[50][51][52]54,55,57,59,60,66,67,76,82,83,85 None of the analyzed studies reported that most respondents had adequate PGx knowledge. In comparison, most studies with pharmacy students found a good or fair level of knowledge among most participants.…”
Section: Knowledge and Awareness Of Pgxmentioning
confidence: 96%